Synthesis and Characterization of Black Currant Selenium Nanoparticles (Part I) - Al-Kurdy, Masar J.; Khudair, Khalisa K.; Al-Kinani, Layla H (The Iraqi Journal of Veterinary Medicine, 2020)
The present study aimed to synthesize selenium nanoparticles (SeNPs) using aqueous extract of black currant as a reducing agent. The green synthesized black currant selenium nanoparticles (BCSeNPs) were identified by color change. The characterization of SeNPs was achieved by Ultraviolet-visible (UV–VIS) spectroscopy, scanning electron microscopy (SEM), X–ray diffraction analysis (XRD), and Fourier transform infrared spectroscopy (FTIR). These tests were used to detect: stability, morphology, size, crystalline nature, and functional groups present on the surface of BCSeNPs. The results revealed appearance of the brick-red color indicating the specific color of selenium nanoparticles, and UV-Vis spectroscopy showed band absorbance at 265 nm of intense surface plasmon resonance manifesting the formation and stability of the prepared BCSeNPs. The SEM image showed the prevalence of spherical selenium nanosized, XRD at 2θ revealed crystallin selenium nanoparticles, the size was in the average of 18-50 nm. Furthermore, FTIR revealed the presence of functional groups of the plant which act as stabilizing and reducing agents. In conclusion, the aqueous black currant extract can act as a reducing and capping agent to synthesize BCSeNPs in nano-scale size by a simple method